Some remarks on bioethics and health care as responsibility to life and nature - Lorenzini Erdmann, Alacoque; Schaefer Ferreira de Mello, Ana Lúcia; Macêdo de Sousa, Francisca Georgina; Santos Koerich, Magda (O Mundo da Saúde, 2006)
There emerges in the field of Bioethics, a discipline and an area of Applied Ethics, the need of a reflection on the health care area including the ethics of care organization and distribution/commercialization. This theme is presented in a proposal for articulating Bioethics with health sector in the research and health care dimensions. The authors follow a reflexive path for thinking in bioethical terms about problems of “knowing how to do” coming from techno-bio-science evolution, as well as about the values inherent to life and health. The reflections on health care in prospective terms made possible the recognition of another value to inspire humanity’s path: caring as an act of responsibility to life and concrete guarantee of healthy living rights. The caring act allows us to cultivate life, to promote the best-living process, respecting and living together with nature, as co-participants in the construction of human civility, in the possibilities of using together/taking from nature the pleasures that life provides us. Our rights and duties to life and nature as citizens, in the social spaces of individual and collective domain, permeate our life and nature caring. KEYWORDS: Bioethics; Ethics ;Health care